Experimental study on the cylindrical oscillating water column device. (15th February 2022) - Li, Yanni; Liu, Shangze; Xu, Chuanli; Li, Demin; Shi, Hongda
Abstract: Wave energy, as a type of high-density renewable energy, has great potential to reduce human dependence on fossil fuels. Integrating wave energy converters (WECs) with mature structures such as breakwaters and offshore wind turbines is a promising concept for wave energy utilization. These technologies reduce the costs of WECs while improving their reliability. In this study, a cylindrical oscillating water column (OWC) device that can be integrated into a monopile-mounted offshore wind turbine (OWT) was experimentally investigated, considering the effects of various parameters including incident wave condition, geometry of the air chamber, and power take-off damping. The results showed that there is an optimal wave condition to maximize the capture width ratio (CWR), regardless of whether the maximum pneumatic power is obtained. A shallow submerged depth of the opening promotes energy extraction under a wider band. The results also illustrated that the optimal opening ratio between the cross-sectional areas of the orifice and air chamber is approximately 1.25%, and when the dimensionless wave frequency is less than 2.4, the CWR increases with the radius of the air chamber. This study provides experimental data with which to validate the numerical models developed for OWC. Highlights: ● A cylindrical OWC and OWT integrating system is proposed. ● A 3D physical model test is developed to study the hydrodynamic performance of the device. ● Effects of wave condition, geometrical parameters of the air chamber and the PTO damping are investigated. ● A shallower submerged depth leads to a wider and smoother efficiency band. ● The larger radius of the chamber offers higher peak of the efficiency.